Immunohistochemical Analysis of Brainstem Lesions in the Autopsy Cases with Severe Motor and Intellectual Disabilities Showing Sudden Unexplained Death - Hayashi, Masaharu; Sakuma, Hiroshi (Frontiers in Neurology, 2016)
It is known that patients with severe motor and intellectual disabilities (SMID) showed sudden unexplained death (SUD), in which autopsy failed to identify causes of death. Although the involvement of brainstem dysfunction is speculated, the detailed neuropathological analysis still remains to be performed. In order to clarify pathogenesis, we investigated the brainstem functions in autopsy cases of SMID showing SUD. We immunohistochemically examined expressions of tyrosine hydroxylase, tryptophan hydroxylase, substance P, methionine-enkephalin, and c-fos in the serial sections of the midbrain, pons, and medulla oblongata in eight SUD cases and seven controls, having neither unexplained death nor pathological changes in the brain. Expressions of tyrosine hydroxylase and tryptophan hydroxylase were reduced in two of eight cases, and those of substance P and/or methionine-enkephalin were augmented in the pons and medulla oblongata in seven of eight cases, including the aforementioned two cases, when compared with those in controls. The hypoglossal nucleus and/or the dorsal vagal nucleus demonstrated increased neuronal immunoreactivity for c-fos in seven of eight cases, although there was no neuronal loss or gliosis in both the nuclei. Controls rarely showed immunoreactivity for c-fos in the medulla oblongata. These data suggest the possible involvement of brainstem dysfunction in SUD in patients with SMID, and consecutive neurophysiological evaluation of brainstem functions, such as all-night polysomnography and blink reflex, may be useful for the prevention of SUD, because some parameters in the neurophysiological examination are known to be related to the brainstem catecholamine neurons and the spinal tract nucleus of trigeminal nerve.